2020
DOI: 10.1101/2020.06.23.20138107
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge about COVID-19 and patients’ beliefs about and use of herbal products during the COVID-19 pandemic: a cross-sectional study in Saudi Arabia

Abstract: The lack of treatment options for COVID-19 has raised many concerns among populations worldwide, which has led to many attempts to find alternative options to prevent the transmission of the disease or to alleviate the progression of the infection, including focusing more on preventive measures (to prevent transmission to other individuals) and the use of natural products and herbal extracts to increase immunity and decrease the probability of getting infected. This study explored the knowledge of the populati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
2
10
0
1
Order By: Relevance
“…However, respondents’ attitude scores were higher than in the study conducted in Bangladesh [ 21 ]. In our study, positive attitude scores were significantly increased among employed and married; these results are in line with several studies conducted in Saudi Arabia [ 3 , 4 , 18 ]. Moreover, the majority of married and employed individuals in our study were elderly, who are known to have increased positive attitudes towards the prevention of COVID-19.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, respondents’ attitude scores were higher than in the study conducted in Bangladesh [ 21 ]. In our study, positive attitude scores were significantly increased among employed and married; these results are in line with several studies conducted in Saudi Arabia [ 3 , 4 , 18 ]. Moreover, the majority of married and employed individuals in our study were elderly, who are known to have increased positive attitudes towards the prevention of COVID-19.…”
Section: Discussionsupporting
confidence: 93%
“…The knowledge of respondents was relatively good, similar to the findings of most studies conducted in several countries [ 18 , 19 ]. This finding could be due to ongoing awareness campaigns conducted by the Ministry of Health (MOH) on combating the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…A similar result was found in several studies that indicate females, and older had a positive attitude and practice compared to males and younger, which is contracted with the study conducted in Tanzanian; they found no significant differences across genders towards an attitude of COVID-19. 19,23,[25][26][27][28] This might be due to females, and older always have positive beliefs and practices toward their health. Furthermore, housewife and employed had significantly better attitudes and practice against the prevention of COVID-19 compared to the students.…”
Section: Discussionmentioning
confidence: 99%
“…Bearing this in mind, on March 2, 2020, before the first case of COVID-19 was detected in Saudi Arabia (Alyami et al, 2020), the nation became one of the first countries to implement early and unparalleled security to deter or alleviate the spread of the disease on its soil. This included school closures and mandatory online distance education.…”
Section: Saudi Context and Global Pandemic Responsementioning
confidence: 99%